2020
DOI: 10.1007/s10393-020-01481-0
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Global One Health Workforce: The “Rx One Health Summer Institute” Approach

Abstract: The One Health approach has gained support across a range of disciplines; however, training opportunities for professionals seeking to operationalize the interdisciplinary approach are limited. Academic institutions, through the development of high-quality, experiential training programs that focus on the application of professional competencies, can increase accessibility to One Health education. The Rx One Health Summer Institute, jointly led by US and East African partners, provides a model for such a progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
1
6
0
2
Order By: Relevance
“…Few medical schools offer OH training programs that are truly interdisciplinary [ 16 , 17 ]. However, increasing accessibility to OH education can be achieved through high-quality experiential training programs that apply OH core competencies [ 9 , 14 , 15 ] and collaborative problem solving with diverse participants [ 23 , 24 ]. Mor et al described a successful OH experiential training experience for veterinary students using a local parklands area as the backdrop for OH scenarios [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few medical schools offer OH training programs that are truly interdisciplinary [ 16 , 17 ]. However, increasing accessibility to OH education can be achieved through high-quality experiential training programs that apply OH core competencies [ 9 , 14 , 15 ] and collaborative problem solving with diverse participants [ 23 , 24 ]. Mor et al described a successful OH experiential training experience for veterinary students using a local parklands area as the backdrop for OH scenarios [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported that application-based trainings were highly effective for learning implementation of One Health while building a stronger public health workforce capacity. 23 Veterinarians with human health professions have an opportunity to raise awareness and hold a collaborative training forum on these animal welfare, One Health, and One Welfare topics at various continuing education venues (eg, American Public Health Association annual meeting, annual USPHS Scientific and Training Symposium). In addition, considerations for pets can be addressed during emergency preparedness planning as documented in the literature 10 or in emergency response policies, as USPHS officers had reported doing.…”
Section: Discussionmentioning
confidence: 99%
“…The in-depth interview guide elicited information on what makes it possible for the employee’s organisation to apply a multidisciplinary approach in solving day to day programmatic challenges, whether the employee’s organisational culture supports a multi-disciplinary approach to solving day to day challenges, steps taken by the employee’s organisation to promote the one health approach, and what makes it difficult to promote a multidisciplinary approach to solving health challenges in the employee’s workplace. The questions contained in the in-depth interview guide were developed after a critical review of literature on barriers and facilitators of effective implementation of the one health approach [ 27 , 40 42 ]. After the development of the interview guide, it was pretested among 4 AFROHUN alumni of the 2019 cohort to ensure that the questions were clear and well-understood prior to the main data collection phase.…”
Section: Methodsmentioning
confidence: 99%
“…Given the role of the OH approach in solving global health challenges, academic institutions and OH-oriented networks continue to develop curricula that aim to empower pre-and in-service professionals with OH-related knowledge, skills and competencies [ 24 27 ]. With funding from the United States Agency for International Development (USAID), AFROHUN, which is a network of 27 institutions of veterinary and public health in the East, Central and West African region is currently championing the development of the OH workforce in ten African countries, including Uganda, Kenya, Rwanda, the Democratic Republic of Congo (DRC), Ethiopia, Tanzania, Cameroon, Liberia, and Senegal.…”
Section: Introductionmentioning
confidence: 99%